2007
DOI: 10.1152/ajpregu.00142.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the external urethral sphincter central pattern generator by a 5-HT1A receptor agonist in rats with chronic spinal cord injury

Abstract: We recently demonstrated that treatment with the 5-HT(1A/7) receptor agonist [(R)-(+)-8-hydroxy-2-di-n-propylamino]tetralin (8-OH-DPAT) increases bladder capacity in chloralose-anesthetized female cats with chronic spinal cord injury. In the current study, we investigated the effects of 8-OH-DPAT on bladder capacity and external urethral sphincter (EUS) activity in urethane-anesthetized female rats (initial body mass 175-200 g) with chronic spinal cord injury (transsection at T10). Cystometric study took place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 30 publications
(31 reference statements)
5
66
1
Order By: Relevance
“…Marson 15 and Lee et al 16 found that neurons in the dorsal gray commissure activated with the pudendal or pelvic nerve stimulation might integrate afferent signal neurons within multiple spinal segments and relay important sensory information to the brain in spinally intact rats. On the other hand, Dolber et al 17 and Chang et al 11 proposed a hypothetical framework for the coordinated bladder contraction and bursting EUS relaxation in the SCI rats including a capsaicin-insensitive afferent input to a switch, which directly or indirectly controls excitation of the parasympathetic preganlionic neurons and relaxation of the Onuf's nucleus motor neurons. In our study, BMSCs in the dorsal gray commissure, presenting proximal to both the sacral parasympathetic preganglionic neurons and the spinal EUS pattern generator, may promote the formation of the switch to coordinate bladder contraction and EUS relaxation by expressing neuronal and astroglial markers 18 or secreting neurotrophic factor and cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Marson 15 and Lee et al 16 found that neurons in the dorsal gray commissure activated with the pudendal or pelvic nerve stimulation might integrate afferent signal neurons within multiple spinal segments and relay important sensory information to the brain in spinally intact rats. On the other hand, Dolber et al 17 and Chang et al 11 proposed a hypothetical framework for the coordinated bladder contraction and bursting EUS relaxation in the SCI rats including a capsaicin-insensitive afferent input to a switch, which directly or indirectly controls excitation of the parasympathetic preganlionic neurons and relaxation of the Onuf's nucleus motor neurons. In our study, BMSCs in the dorsal gray commissure, presenting proximal to both the sacral parasympathetic preganglionic neurons and the spinal EUS pattern generator, may promote the formation of the switch to coordinate bladder contraction and EUS relaxation by expressing neuronal and astroglial markers 18 or secreting neurotrophic factor and cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs were administered at previously described doses (7,14,21). The first posttreatment urodynamic examinations were completed within 20 -45 min following drug administration because of the short half-life of 8-OH-DPAT (11,21). Moreover, several rats (n ϭ 5) were used only for determining the independent effects of 8-OH-DPAT and WAY-100635 on urethral smooth muscle activity; these rats were administrated an iv injection of ␣-bungarotoxin (0.4 mg/kg, dissolved in saline) ϳ30 min before the 8-OH-DPAT treatment.…”
Section: Drug Administrationmentioning
confidence: 99%
“…In this study, WAY-100635 was administered to the rats at intervals of Ͼ1 h after the 8-OH-DAPT administration because the effect of 8-OH-DAPT had worn off before the WAY-100635 administration due to the short half-life of 8-OH-DPAT (ϳ20 -30 min) in rats (11,21). Thus we did not detect any drug effects of WAY-100635 interacted with 8-OH-DPAT treatment in the present study.…”
Section: Effects Of 8-oh-dpat (03 Mg/kg Iv) and Way-100635 (01 Mg/kmentioning
confidence: 99%
See 1 more Smart Citation
“…The EUS bursting is initially eliminated by transection of the thoracic spinal cord (98) but recovers in chronic spinal animals as a result of reorganization of spinal reflex circuitry ( Fig. 14) (97,98,104,194). In the rat recordings of single EUS motor units as well as intracellular recordings from EUS motoneurons revealed tonic and burst firing in some units and primarily burst firing in others, raising the possibility of two separate excitatory inputs to EUS motoneurons that allow some to contribute to storage and voiding and others to contribute primarily to voiding (129).…”
Section: Subcortical Urine Storage Mechanismsmentioning
confidence: 99%